Impact of Price Increase and Discount Strategies on Supply Chain Profit under the Reference Price Effect - Pan, Fei; Jiang, Zhenyang; Zheng, Qi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Products sold to the market typically go through the introductory and maturity stages. The increase in general market demand during the maturity stage leads retailers to adopt a price increase strategy to boost profits. However, when the price is higher than the psychologically acceptable reference point of the consumers, they may perceive the transaction as unfair, leading them to abandon the transaction and thereby reduce demand. At this time, if retailers consider the reference price effect in advance and adopt the discount strategy, consumers will take the first-stage price as a reference point, which will instead have a psychologically positive effect and increase demand. To investigate the impact of these two strategies on supply chain profits, we construct models for price increase and discount strategies that consider the reference price effect and compare the profit differences of manufacturers, retailers, and the supply chain in centralized and decentralized scenarios. Results reveal that, in centralized decision-making, a threshold exists for the retailer adopting either the price increase or decrease strategy. However, in decentralized decision-making, retailers will always adopt the price increase strategy. In addition, in centralized decision-making, the presence of consumers sensitive to price fairness will always reduce the overall profit of the supply chain. However, it is counterintuitive that under certain parameter constraints in decentralized decision-making, the presence of such consumers may increase the overall profit of the supply chain.